Eribulin Monotherapy in Patients Aged 70 Years and Older With Metastatic Breast Cancer. (28th March 2014) - Muss, Hyman; Cortes, Javier; Vahdat, Linda T.; Cardoso, Fatima; Twelves, Chris; Wanders, Jantien; Dutcus, Corina E.; Yang, Jay; Seegobin, Seth; O'Shaughnessy, Joyce
Abstract : Purpose: Following the demonstrated efficacy and safety of eribulin mesylate in heavily pretreated patients with metastatic breast cancer, an exploratory analysis was performed to investigate the effect of age in these patients. Methods: Data were pooled from two single‐arm phase II studies and one open‐label randomized phase III study in which patients received eribulin mesylate at 1.4 mg/m 2 as 2‐ to 5‐minute intravenous infusions on days 1 and 8 of a 21‐day cycle. The effect of age on median overall survival (OS), progression‐free survival (PFS), overall response rate (ORR), clinical benefit rate (CBR), and incidence of adverse events (AEs) was calculated for four age groups (<50 years, 50–59 years, 60–69 years, ≥70 years). Results: Overall, 827 patients were included in the analysis (<50 years, n = 253; 50–59 years, n = 289; 60–69 years, n = 206; ≥70 years, n = 79). Age had no significant impact on OS (11.8 months, 12.3 months, 11.7 months, and 12.5 months, respectively; p = .82), PFS (3.5 months, 2.9 months, 3.8 months, and 4.0 months, respectively; p = .42), ORR (12.7%, 12.5%, 6.3%, and 10.1%, respectively), or CBR (20.2%, 20.8%, 20.4%, and 21.5%, respectively). Although some AEs had higher incidence in either the youngest or the oldest subgroup, there was no overall effect of age on the incidence of AEs (including neuropathy, neutropenia, and leukopenia). Conclusion: Eribulin monotherapy in these selected older patients with good baseline performance status led to OS, PFS, ORR, CBR, and tolerability similar to those of younger patients with metastatic breast cancer. The benefits and risks of eribulin appear to be similar across age groups. Abstract : This exploratory analysis of pooled data from selected older patients with pretreated metastatic breast cancer in phase II and III clinical trials showed similar efficacy and tolerability for eribulin mesylate among patients who were 70 years of age or older when compared with younger patient subgroups. These data indicate that eribulin may be an effective option for older patients. Abstract : 摘要 目的 甲磺酸艾日布林的疗效和安全性在曾接受过大量预先治疗的转移性乳腺癌患者中得到证实，本文作者在此基础上进行了一项探索性分析，以研究年龄在这些患者中会产生何种影响。 方法 汇总了两项单组 II 期研究和一项开放标签随机 III 期研究的数据，这些研究中患者在 21 天一个周期的第 1 和第 8 天，以 2 至 5 分钟静脉输注的方式按 1.4 mg/m 2 的剂量接受甲磺酸艾日布林治疗。针对四个年龄组（<50 岁、50–59 岁、60–69 岁、≥70 岁）计算了年龄对中位整体生存期（OS）、无疾病进展生存期 （PFS）、总见效率（ORR）、临床受益率（CBR）和不良事件（AE）发生率的影响。 结果 总共827 名患者被纳入分析（<50 岁， n = 253；50–59 岁， n = 289；60–69 岁， n = 206；≥70 岁， n = 79）。年龄对 OS（分别为 11.8 个月、12.3 个月、11.7 个月和 12.5 个月； p =.82）、PFS（分别为 3.5 个月、2.9 个月、3.8 个月和 4.0 个月； p = .42）、ORR（分别为 12.7%、12.5%、6.3% 和 10.1%）或 CBR（分别为 20.2%、20.8%、20.4% 和 21.5%）没有显著影响。虽然在年纪最小或年纪最大的亚组中有些 AE 的发生率较高，但是总体上年龄对 AE（包括神经病变、中性粒细胞减少症和白细胞减少症）发生率没有影响。 结论 这些选定的、基线体能状况良好的年纪较大患者使用艾日布林单药疗法所产生的 OS、PFS、ORR、CBR 和耐受性与年纪较小的转移性乳腺癌患者相似。艾日布林的益处和风险在各年龄组之间看似相似。 The Oncologist 2014; 19:318–327